ANALYSIS OF THE SETTLEMENT OF THE WORSHIP PENALTY AGAINST ACTION OF JINAYAH MAISIR’S IN ACEH - Muhammad Nasir; Hamdani Hamdani (Geuthèë Institute, Aceh, 2022)
The implementation of Islamic jinayah law in Aceh Province applies only to the actions of jinayah maisir (gambling), khamar and khalwat, as well as hudud, whereas the acts of jinayah qisas and diyat have not been enforced. This study analyzed the cases that were decided by the Aceh Syariah Court in 2005 and 2006 based on Qanun Aceh Province Number 13 of 2003 about Jinayah Maisir (Gambling) which was then currently enacted Qanun No 6 of 2014. The study uses a qualitative methodology with a legal approach and a case approach. This study found that the court, which convicted the court in connection with the jinayah of the maisir act, showed that the allocation of ta'zir punishment on maisir offenders according to Qanun Aceh Province Number 13 of 2003 About Maisir (Gambling) is in line with the requirements of ta'zir in Islam. It is recommended to the judges in the court to continue to adhere to the Islamic and legal provisions that exist in deciding sharia law matters in Aceh